الأنساق الثقافية في رواية امرأة عند نقطة الصفر موت الرجل الوحيد على الأرض لنوال السعداوي "أنموذجا " - بوصبيع ابراهيم, نور; زنقي, نعيمة; جبالي, الشيماء (جامعة الوادي - University of Eloued, 2023)
يهدف بحثنا إلى دراسة الأنساق الثقافية في الرواية وتتبع سيرورتها، لذلك وسمنا مذكرتنا "بالأنساق الثقافية في رواية امرأة عند نقطة الصفر موت الرجل الوحيد على الأرض لنوال السعداوي" حيث وجدنا أنساقا ثقافية بارزة كنسق اللغة والعنف والسلطة المستبدة ونسق المتاجرة بالأجساد... وقد أسهمت العديد من النقاد في إكتشاف الأنساق الثقافية المضمرة التي ظهرت وتجسدت عبر مكونات السرد، والمواقف والقيم، والأفكار التي احتواها المتن الروائي. Abstract : Our research aims at studying the cultural patterns in the novel and following its course, so researchers called our study by "the cultural patterns in the novel of a woman at Ground Zero, the death of the only man on Earth by Nawal al-Saadawi" where we found prominent cultural patterns such as language, violence, authoritarian power and the pattern of trafficking in bodies. Many critics have contributed to the discovery of implicit cultural patterns that emerged and materialized through the narrative components, attitudes, values, and ideas contained in the narrative body.